Digital Papillary Adenocarcinoma: Uncommon Malignancy of Sweat Glands - Two Rare Cases - Neeti Goyal; Pawan Dhaman; Jasvinder Kaur Bhatia; Pragya Sharma; Prabha Shankar Mishra; Vikram Singh; Anvesh Rathore (Journal of Marine Medical Society)
Background: Digital papillary adenocarcinoma (DPA) is a very rare malignant tumor of the sweat glands originally described by Helwig in 1979.It often presents as a solitary painless mass, commonly found on the volar surface of the fingers and toes and the adjacent skin of the palms and soles. Materials and Methods: Two rare cases of DPA in 43- and 48-year-old male patients who presented with swelling finger were included over period of one year study in a tertiary care hospital. Results: Our study had two cases with male patient of age 48 year and 43 year old. Both presented with swelling and a mass lesion left middle finger, past 8 years and nodule in proximal phalangeal region of left index finger for 15 years respectively. On histomorphology and immunohistochemistry both were diagnosed as DPA. Conclusion: DPA is a rare adnexal tumor which generally present for months to years before the patient seeks medical attention. Careful evaluation with early surgical removal and accurate histological diagnosis is must when managing patients with DPA as these can be aggressive and even result in metastasis.